2013
DOI: 10.1093/ageing/aft197
|View full text |Cite
|
Sign up to set email alerts
|

BODE index or geriatric multidimensional assessment for the prediction of very-long-term mortality in elderly patients with chronic obstructive pulmonary disease? A prospective cohort study

Abstract: : Both the 'classic' MDA and the BODE index are comparably associated with mortality, even at very long term, in elderly people with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…Pendone C et al, 7 found in their study that the mean age of the patients was 73.3 years and the male to female ratio was 3.29:1 which is in accordance to the findings of the present study. 7 Ko FW et al, found a higher male to female ratio in their study and they reported that it was 5.94:1 which is higher than the findings of the present study. 8 "The lung health study" was carried out in people who smoked and were aged 35-60 years of age and it was found that they had obstruction in the airway which was of mild to moderate in nature.…”
Section: Discussioncontrasting
confidence: 70%
“…Pendone C et al, 7 found in their study that the mean age of the patients was 73.3 years and the male to female ratio was 3.29:1 which is in accordance to the findings of the present study. 7 Ko FW et al, found a higher male to female ratio in their study and they reported that it was 5.94:1 which is higher than the findings of the present study. 8 "The lung health study" was carried out in people who smoked and were aged 35-60 years of age and it was found that they had obstruction in the airway which was of mild to moderate in nature.…”
Section: Discussioncontrasting
confidence: 70%
“…Supplementary table F shows all the external validation studies of the prognostic models for outcome prediction in COPD patients 2325 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, multidimensional scores have been introduced in order to better assess COPD outcomes, particularly the mortality risk, even if results were variable due to their different specificity and sensitivity [3,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. The vast majority of studies have stated that exacerbations represent the main driver of COPD burden because they can affect morbidity, quality of life, hospitalizations, mortality, and related healthcare expenditure [24,25,26,27,28].…”
Section: Cost Trends In Real Lifementioning
confidence: 99%